2018
DOI: 10.1177/2333721418781668
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use Among Adults 50 Years or Older in the 21st Century

Abstract: Background: Marijuana is the most commonly used illicit drug among older adults. As an older population grows in the United States that has a tolerant attitude toward marijuana use, the dynamics of marijuana use and the effects of marijuana on personal, social, and health outcomes among older adults require attention. Objectives: This review summarizes epidemiological literature on marijuana use among older adults. Method: A literature search was conducted using PubMed, AgeLine, and an online search engine fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 62 publications
2
61
0
2
Order By: Relevance
“…In the absence of clinical trial data for medical cannabis use, largely due to cannabis still being a Schedule I substance, epidemiological studies may be helpful in understanding how older adults are currently using medical cannabis. A number of epidemiological studies from national surveys examining patterns of cannabis use in older adults already exist 1,[15][16][17][18] -studies document a significant increase in cannabis use by older people over the past two decades, 1,17,18 with one study by Han and Palamar showing that among U.S. older adults age 65 + years, there was an increase in the use of cannabis from 2.4% in 2015 to 4.2% in 2018. 1 A number of reasons for these increases have been proposed, including changing attitudes of cannabis among older people, changes in the legal status in individual states, and unique health care needs of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of clinical trial data for medical cannabis use, largely due to cannabis still being a Schedule I substance, epidemiological studies may be helpful in understanding how older adults are currently using medical cannabis. A number of epidemiological studies from national surveys examining patterns of cannabis use in older adults already exist 1,[15][16][17][18] -studies document a significant increase in cannabis use by older people over the past two decades, 1,17,18 with one study by Han and Palamar showing that among U.S. older adults age 65 + years, there was an increase in the use of cannabis from 2.4% in 2015 to 4.2% in 2018. 1 A number of reasons for these increases have been proposed, including changing attitudes of cannabis among older people, changes in the legal status in individual states, and unique health care needs of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has suggested that a higher frequency of cannabis use is significantly associated with an increased probability of reporting alcohol use disorder (Blazer and Wu 2009). This study, however, examined older adults (aged 50 or older) (Lloyd and Striley 2018), who have different characteristics than younger population. The current study found that, compared to those who reported no lifetime cannabis use, adolescents and youths with less frequent cannabis use (1-20 days/month) are more likely to report alcohol dependence and alcohol-associated adverse effects.…”
Section: Discussionmentioning
confidence: 96%
“…Electronic cigarette (e-cigarette) and marijuana use has been increasing among cigarette smokers with or at risk for COPD 7,8 . The longterm impact of the consumption of such products is still being investigated.…”
Section: Exposuresmentioning
confidence: 99%